Brightest cluster galaxy properties and the relaxation of galaxy clusters in the IllustrisTNG simulations - Kelder, Kelly (My University, 2025)
Brightest cluster galaxies (BCGs) are the predominant component of galaxy clusters which serve as important tracers for galactic and cosmic evolution. They are a powerful probe for estimating the dark matter and dark energy content of the Universe via their mass function. Insight into the dynamical state of the cluster, which is needed to investigate these relations, can be offered through the positions, kinematics, and structural characteristics of their BCGs. In this thesis, the properties of BCGs are analyzed using the TNG300-1 run of the IllustrisTNG cosmological hydrodynamical simulation project. The study focuses on the relation of BCGs to its host cluster mass, dynamics, and substructuring. A variety of observationally motivated indicators, such as the magnitude gap, peculiar velocities, and BCG central offsets, are used to explore the relaxation of these galaxy clusters. The analysis confirmed that BCG mass and half-mass radius strongly correlate with the corresponding properties of its host cluster, implying that the BCG growth rate is directly related to the growth of the cluster. Dynamical analysis revealed that the majority of BCGs reside near the cluster potential well, with over 95% of them having an offset smaller than their half-mass radius. Comparisons across redshift demonstrate a clear trend toward increased BCG centrality and dynamical relaxation over time. As a comparison, clusters with greater BCG offsets in the current epoch show to have a narrow magnitude gap, indicating dynamical disturbances and possible substructuring within them. The analysis of cluster substructures, done via Gaussian mixture modeling, showed that most commonly (in ∼ 30% of the cases) these systems exhibited two substructures, implying again that the entire set of clusters cannot be assumed to be dynamically relaxed. When applying the virial theorem and center of mass shift criteria, around 20% of clusters at z = 0 are considered to be in dynamical equilibrium, reinforcing the need for careful consideration of dynamical state in both simulation and observational studies. These findings contribute to a broader understanding of BCG formation and evolution and offer proxies for evaluating cluster relaxation in future observational work.
Keywords: brightest cluster galaxies, cluster dynamics, hydrodynamical simulations